1990
DOI: 10.1139/x90-235
|View full text |Cite
|
Sign up to set email alerts
|

Nursery and field fertilization of 2 + 0 ponderosa pine seedlings: the effect on morphology, physiology, and field performance

Abstract: Ponderosa pine (Pinusponderosa Laws.) from two seed zones in central Oregon were grown at two nurseries where they were subjected to fall applications of N, N + K, or no fertilizer. For one seed zone, foliar N concentration increased from 1.47 to 1.53% for the N application and to 1.57% for N + K application. For the other seed zone, seedlings did not show any differences in foliar N after nursery fertilization. Seedlings that received the N application appeared to be less susceptible to frost damage, but nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Application of N to dormant slash pine (Irwin et al, 1998), ponderosa pine (Gleason et al, 1990), and Douglas-fir (Margolis and Waring, 1986) seedlings increased N concentration. In our study, six weeks after applying fertilizer to red pine seedlings with dormant terminal buds, shoot and root N concentrations in seedlings receiving 89 kg N ha −1 were 40% and 68% greater than for the control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Application of N to dormant slash pine (Irwin et al, 1998), ponderosa pine (Gleason et al, 1990), and Douglas-fir (Margolis and Waring, 1986) seedlings increased N concentration. In our study, six weeks after applying fertilizer to red pine seedlings with dormant terminal buds, shoot and root N concentrations in seedlings receiving 89 kg N ha −1 were 40% and 68% greater than for the control.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Timmis (1974) reported Douglas-fir seedlings with low foliar N concentration (i.e., 0.8%) had a LT 50 of -13 • C and those with a higher concentration (i.e., 1.6%) had a LT 50 of -30 • C. Gleason et al (1990) reported that fall fertilized ponderosa pine seedlings with a N concentration of 1.55% were more cold hardy than control seedlings with 1.47% N. Fernández et al (2007) observed that N fertilized plants with more than 1.25% N better tolerated freezing than those that had less than 1%. Similarly, Luoranen et al (2008) observed poor autumn cold hardiness for Picea abies seedlings with lower (i.e., 1.1%) compared to higher (i.e., > 1.6%) foliar N concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertilizer may be applied to the planting hole, to an adjacent hole, or surface broadcast [8]. To facilitate nutrient uptake, many researchers have recommended applying CRF directly in the planting hole, such that nutrients are released in the immediate vicinity of the root system [2,12,14,23,52]. However, fertilization in the planting hole may limit root system expansion because roots tend to proliferate in areas 644 D.F.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient loading before hardening may counter late-season dilution [39], although some growers are reluctant to adopt this practice because of concerns that high N fertilization may jeopardize frosthardiness development in seedlings prior to winter storage [2,17,43]. More recent studies, however, have shown that high N supply does not affect cold tolerance of conifers [4] and may actually increase frost-hardiness [7,14,16,27,35]. Presumably autumnal accumulation of free amino acids and proteins may lessen cellular freezing damage by reducing the symplastic water volume [3,26,38].…”
Section: Introductionmentioning
confidence: 99%